Knife - Holders in Ancient Egyptian Tombs (Religious and Artistic Study) - dr.Rasha Omran (Journal of General Union of Arab Archaeologists, 2015)
Studying ancient Egyptian tombs have long been an important source of information regarding many aspects of Egyptian religion. Walls of New Kingdom tombs are often decorated with plenty of painted religious scenes. While they were primarily private structures containing images selected by the person who expected to be housed there for eternity, the funerary monuments also reflect religious beliefs. While numerous researches focused on many of the religious scenes depicted on the walls of ancient Egyptian tombs, no one focused on the knife - holders' scenes. Hence, the current study focused on knife - holders scenes depicted on the walls of both royal and private tombs dating back to the New Kingdom at Thebes. The current study was undertaken to shed light on the meaning and the function of knife in Ancient Egypt. To study the role of the knife-holders in Ancient Egypt. To spot light on the actions and behaviors and locations of the knife-holders in Ancient Egyptian civilization. To spot light on the representations of the knife-holders on the walls of the ancient Egyptians tombs in the Valley of the Kings and Valley of the Queens as well as the private tombs at western Thebes. To focus on the shapes and positions of the Knife-holders in Ancient Egypt. To explain the difference between Knife - Holders and Demons. To achieve the objectives of the study, the required data were collected from periodicals, references presenting Knife Holders scenes. Preserving the scenes of knife - holders on the walls of the royal tombs in the Valley of the Kings and Valley of the Queens dating back to the New Kingdom as well as the private tombs at western Thebes that contributed to the interpretation of all the data gathered from literature. The preliminary results indicated that the term (Knife-Holders) is an expression which indicates to tomb-guardians, demons or minor divinities. These minor deities were subordinate to the major gods and goddesses. They performed specified tasks upon demand and while the major gods tended to be more universal in nature, demons were often defined by specific actions, behaviors and locations. Knife - Holders were often associated with caves, pits and tombs which were considered entrances to the underworld. Moreover, they constituted different categories. Some were clearly portrayed with frightening instruments of punishment like knives for the damned. Others were not antagonistic and may often be classed as minor guardian deities such as the keepers of the various gates of the underworld. Some were creatures specially tasked with the protection of the king or the deceased in the journey through the netherworld. Concerning their forms, Knife-holders are represented in different forms like human forms, half-anthropomorphic with human bodies. They are represented with the heads of different creatures such as jackals, rams and falcons.